2019
DOI: 10.1111/pbi.13171
|View full text |Cite
|
Sign up to set email alerts
|

Strong temporal dynamics of QTL action on plant growth progression revealed through high‐throughput phenotyping in canola

Abstract: SummaryA major challenge of plant biology is to unravel the genetic basis of complex traits. We took advantage of recent technical advances in high‐throughput phenotyping in conjunction with genome‐wide association studies to elucidate genotype–phenotype relationships at high temporal resolution. A diverse Brassica napus population from a commercial breeding programme was analysed by automated non‐invasive phenotyping. Time‐resolved data for early growth‐related traits, including estimated biovolume, projected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 98 publications
3
74
0
Order By: Relevance
“…[ 73 ] were unable to find overlapping QTL when studying barley during the germination and seedling stages, arguing that different tolerance mechanisms could be involved in the different stages. QTL that contribute to a certain trait can have a transient nature and dynamically change with time and developmental stages [ 54 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 73 ] were unable to find overlapping QTL when studying barley during the germination and seedling stages, arguing that different tolerance mechanisms could be involved in the different stages. QTL that contribute to a certain trait can have a transient nature and dynamically change with time and developmental stages [ 54 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the end, the paper was focused on QTL associated with transpiration efficiency [24]. Similarly, Peirone et al [77] found that transpiration efficiency measured in greenhouse conditions at the early stages of soybean growth was the most efficient trait in predicting drought tolerance in the field and Knoch et al [75] showed that early plant growth of canola was a complex trait that involves several temporally dynamic loci with medium and small effects. Furthermore, the heritabilities of TPA-measured traits were relatively low in our experiments, ranging between 0.5 and 0.6 (S6 Table), and these values were based on spatially adjusted means.…”
Section: Plos Onementioning
confidence: 99%
“…In order to effectively control false positives and reduce false negatives, the method iteratively performs marker tests with pseudo-quantitative trait nucleotides (QTNs) as covariates in a fixed-effect model and keeps optimizing pseudo-QTNs in a random-effect model until no new pseudo QTNs are added [34]. The capability of removing confounding effects between testing markers and kinship, preventing model overfitting and controlling false positives enable FarmCPU, has become one of the most efficient methods in current GWAS [36]. In this study, best linear unbiased predictions (BLUPs) of six seedling germination traits collected from the 211 C. sativa accessions and 6192 numerically SNPs [26] were used to perform FarmCPU algorithm in R studio.…”
Section: Genome Wide Association Study (Gwas) Analysesmentioning
confidence: 99%
“…nlm.nih.gov/genome/gdv/browser/?context=genome&acc=GCF_000633955.1) provided by Agriculture and AgriFood Canada. The LD blocks harboring significant trait-associated markers and their flanking markers with strong LD (r 2 > 0.6) were defined as candidate gene regions as suggested by Knoch et al [36]. All genes within the LD blocks were considered for candidate genes and annotated for predictive functions using C. sativa genome annotation database incorporated in snpEff [37].…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…Currently, researchers are also using molecular genetic mapping of QTL of many complex traits vital in plant breeding. The detection and molecular cloning of genes underlying QTL enable the investigation of naturally occurring allelic variations for specific complex traits [85,153]. Plant productivity can be improved by identifying novel alleles through functional genomics or haplotype analysis.…”
Section: Contribution Of Plant Breeding To Crop Improvementmentioning
confidence: 99%